Cucurbituril-based Supramolecular complexes with platinum compounds influence on expression of CTLA-4 on Regulatory T cells - A. A. Aktanova; M. V. Bykova; O. S. Boeva; E. A. Pashkina; L. V. Grishina; V. A. Kozlov (Медицинская иммунология, 2023)
Tumors are a leading pathology in the population. Chemotherapy cannot provide adequately and effectively to cure patients. Some medicine, such as cytostatic, are characterized by a wide range of side effects and resistance of solid tumors to chemotherapy by these medicines. In recent research, the mechanisms of action of cytotoxic agents have been described, and the most appropriate causes of resistance have been suggested. Drug delivery system based on Cucurbit[7]uril (CB[7]) was used to minimize side effects and overcome resistance. CB[7] has ability to form host-guest supramolecular complexes with oxaliplatin and carboplatin.It is important to consider the immune system maintain to a great role, and platinum compounds are able to have an immunomodulatory effect on immunocompetent cells. There is convincing evidence about the cytotoxic response against tumor cells is also associated with immunomodulating properties. A specific immune microenvironment with high frequency of suppressor cells is made by tumors. FoxP3+ regulatory T cells are recruited by the tumor, an increased number of these cells and expression levels of CTLA-4 and PD-1 on them contribute to the progression of the tumor process. These markers correlate with recurrence and poor survival of the patients. Therefore, it is necessary that antitumor therapy agents have an effect on a subpopulation of regulatory T cells and their functional activity. This study evaluated the effects of cucurbit[7] uril, platinum compounds, and supramolecular complexes on FoxP3+ regulatory T cells and the expression of immune checkpoint molecules.In this study peripheral blood cells from volunteers (n = 8, average 29.0±2.4) were used. Mononuclear cells obtained in the standard protocol were incubated for 72 h at concentrations of 0.3 and 0.1 mM for carboplatin and oxaliplatin, respectively, as well as complexes and CB[7] in equivalent dosages. Next, the samples were labeled with monoclonal antibodies to determine the phenotype and expression of immune checkpoint molecules by flow cytometry.We obtained the following results: The CB[7]-carboplatin complex in stimulated and non-stimulated cultures significantly reduced the number of FoxP3+ regulatory T cells compared to the control. At the same time, carboplatin and the CB[7]-carboplatin complex reduced the expression of CTLA-4 in an non-stimulated culture compared to CB[7].Complexes of Cucurbit[7]urils with platinum compounds are a perspective antitumor agent with immunomodulatory properties.